Association between dental diseases and history of stroke in the United States. Issue 5 (2nd April 2021) - Alhadainy, Hatem A.; Keefe, Thomas; Abdel‐Karim, Amany H.; Abdulrab, Saleem; Halboub, Esam
Abstract: Objective: This study aimed to determine the potential association between the dental diseases and self‐reported history of stroke in the United States based on data from the Third National Health and Nutrition Examination Survey (NHANES III). Methods: Data were extracted from NHANES III. Dental variables were carious tooth surfaces, number of missing teeth, gingival bleeding, and periodontal pockets. Multiple logistic regression modeling was used to estimate the effect of these dental diseases on the self‐reported history of stroke with intent to adjust for the other potential determinants: age, sex, race, marital status, health insurance, education, exercise, body mass index, smoking, alcohol, hypertension, high serum cholesterol, and diabetes. Results: Number of missing teeth was found to be significantly associated with the self‐reported history of stroke. Associations between the self‐reported history of stroke and caries, gingival bleeding, or periodontal pockets were not statistically significant. Conclusions: Number of missing teeth was an independent determinant of the self‐reported history of stroke.